Performance and carcass characteristics of different cattle types - May, M.L.; Lipsey, R.J.; Loveday, H.D.; Allen, Dell M.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station, 2011)
Different cattle types were evaluated for growth, feed efficiency, and carcass and meat traits. Hereford, Angus, Jersey, South Devon, Limousin, Simmental, and Charolais sires were bred artificially to Angus and Hereford dams to obtain different cattle types. Three calf crops were born in March, Apri1, and May of 1970, 1971, and 1972 and were weaned when 200 days old. All male calves (1,123) were castrated, fed out and slaughtered in a commercial slaughter plant. Carcass cooler data were obtained and the right side transported to Kansas State University for detailed cut-out and meat quality evaluations.
Keywords: Beef; Performance; Carcass characteristics; Cattle breeds; Growth; Feed efficiency